2009
DOI: 10.1088/0004-637x/694/2/1498
|View full text |Cite
|
Sign up to set email alerts
|

The Acs Survey of Galactic Globular Clusters. Vii. Relative Ages

Abstract: The ACS Survey of Galactic globular clusters is a Hubble Space Telescope Treasury program designed to provide a new large, deep, and homogeneous photometric database. Based on observations from this program, we have measured precise relative ages for a sample of 64 Galactic globular clusters by comparing the relative position of the clusters' main-sequence (MS) turnoffs, using MS fitting to cross-compare clusters within the sample. This method provides relative ages to a formal precision of 2%-7%. We demonstra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

61
552
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(615 citation statements)
references
References 64 publications
61
552
2
Order By: Relevance
“…Further supporting evidence for the external origin of the halo GCs in the Milky Way is found by analysing their ages, metallicities, kinematics, horizontal branch morphologies, luminosities, and sizes; they are all consistent with the predictions of hierarchical formation models (e.g. Mackey & Gilmore 2004;Mackey & van den Bergh 2005;Marín-Franch et al 2009;Forbes et al 2010;Dotter et al 2011;Keller et al 2012).…”
Section: Introductionsupporting
confidence: 63%
“…Further supporting evidence for the external origin of the halo GCs in the Milky Way is found by analysing their ages, metallicities, kinematics, horizontal branch morphologies, luminosities, and sizes; they are all consistent with the predictions of hierarchical formation models (e.g. Mackey & Gilmore 2004;Mackey & van den Bergh 2005;Marín-Franch et al 2009;Forbes et al 2010;Dotter et al 2011;Keller et al 2012).…”
Section: Introductionsupporting
confidence: 63%
“…Published work (e.g. Gratton et al 2003;De Angeli et al 2005;Hansen et al 2007;Marín-Franch et al 2009; among many others) indicates that the absolute age of the metal-poor clusters is near 13 Gyr and shows a cluster-to-cluster dispersion that may be as low as ±0.5 Gyr, confirming their classic status as among the first stellar structures to have formed in the galaxy. The mean age for the metal-richer subsystem is perhaps 2 Gyr younger than the extremely old, metal-poor subsystem, and exhibits a higher cluster-to-cluster age scatter, near ±2 Gyr rms.…”
Section: Age Distributions and Galaxy Formationmentioning
confidence: 77%
“…Past observations have shown that galactic metal-poor GCs tend to be older than metal-rich GCs and the age spread in metal-poor GCs is ∼ 1 Gyr compared to the ∼ 6 Gyr dispersion in metal-rich GCs (Rosenberg et al 1999;Salaris & Weiss 2002;Marín-Franch et al 2009). There is some evidence of self enrichment in GCs; however, the age gap between metal-poor and metal-rich GCs is greater than the range present within each population suggesting that these are two distinct populations (Marín-Franch et al 2009).…”
mentioning
confidence: 96%
“…There is some evidence of self enrichment in GCs; however, the age gap between metal-poor and metal-rich GCs is greater than the range present within each population suggesting that these are two distinct populations (Marín-Franch et al 2009). However, more recent observations have shown a gradual trend of increasing age spread with increasing metallicity which weakens this age gap described in the previous works (Dotter et al 2011;VandenBerg et al 2013).…”
mentioning
confidence: 99%